High Resolution Site Characterization as key element for proper design and cost estimation of groundwater remediation - Pieter Dijkshoorn; Piero Mori; Mattia Cappelletti Zaffaroni (Acque Sotterranee, 2014)
Substantial amounts of money are spent each year on cleaning up ground water contaminations that were caused by historical industrial site activities. Too often, however, remedial objectives are not achieved within the anticipated time frame. Moreover, remedial budgets which were estimated prior to the start of remediation turn out to be largely insufficient to meet the remedial objectives. This situation, very common, creates significant troubles for all the stakeholders involved in the remediation project. The reason for not meeting remedial regulatory closure criteria or exceeding remedial budgets is often due to an incomplete conceptual site model. Having conducted high resolution site characterization programs at numerous sites where remediation was previously conducted, ERM has found several recurring themes: • Missed source areas and plumes; • Inadequate understanding of source area and plume architectures (i.e., three-dimensional contaminant distribution); • Inadequate understanding of the effects of site (hydro)geologic conditions on the ability to access contamination (i.e., via remedial additive injections of groundwater/soil gas extraction). This paper explains why remediations often fail and what the alternatives to prevent these failures (and exceeding remedial budgets) are. More specifically, it focuses on alternative investigation methods and approaches that help to get to a more complete (high resolution) conceptual site model. This more complete conceptual site model in return helps a more focused remedial design with a higher remedial efficiency. As a minimum, it will take away a lot of (financial) uncertainty during the decision making when selecting a remedial alternative. Contaminants that have a greater density then water are known to have a greater complexity in terms of both investigation as well as remediation. Therefore, they will be the main focus of this paper.